Removal of Pollutants from Water Using Untreated and Treated Sawdust and Water Hyacinth - Th. El-Nabarawy; S.A. Khedr (Adsorption Science & Technology)
Sawdust and water hyacinth are waste products which have no economical application in Egypt. They even constitute a solid waste as far as the environment is concerned. As-received sawdust and water hyacinth were treated with phosphoric acid, phosphoric acid + urea or phosphoric acid + urea + dimethylformamide. The as-received and treated samples were used for the removal of Methylene Blue, iodine, phenol and ammonia from their aqueous solutions. The optimum conditions for the maximum adsorption of each pollutant were determined. The isotherms obtained obeyed the Freundlich and Langmuir equations in a satisfactory manner. The initial stages of adsorption follow first-order kinetics as predicted from the Lagergren equation. Sawdust and water hyacinth show promising potentialities for the removal of pollutants from water and can, at least, be used as precursors for the preparation of efficient adsorbents for the removal of pollutants from water.